The Catalytic Performance of Vanadium–Nickel Supported on Zeolite for the Conversion of Crude Palm Oil into Short-Chain Hydrocarbons - Rahmahwati, Cut Aja; Salmyah, Salmyah; Sami, Muhammad; Sariadi, Sariadi (Jurnal Teknologi, 2025)
The increasing global demand for fossil fuels, alongside declining domestic oil production, has intensified interest in renewable energy sources. Among Indonesia's abundant biomass options, crude palm oil (CPO) is a promising candidate for biofuel production due to its high triglyceride content and chemical similarity to petroleum. This study explores the catalytic cracking of CPO using a vanadium–nickel catalyst supported on natural zeolite, aiming to evaluate its physicochemical properties and catalytic performance in converting CPO into short-chain hydrocarbons for potential use as biogasoline. The catalyst was synthesized via wet impregnation of natural zeolite with ammonium metavanadate and nickel nitrate hexahydrate, followed by calcination. Characterization using Thermogravimetric Analysis (TGA), X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) confirmed good thermal stability, crystallinity, and surface morphology. Catalytic cracking was performed at elevated temperatures under atmospheric pressure. The liquid products were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that the catalyst successfully facilitated the breakdown of triglycerides, producing mainly medium-chain fatty acids. Pentadecanoic acid (C₁₅H₃₀O₂) was identified as the dominant compound, indicating partial cracking of CPO. However, the product composition still contained oxygenated species, suggesting incomplete deoxygenation. Consequently, the resulting mixture does not yet meet biogasoline specifications. These findings highlight the potential of vanadium–nickel/zeolite catalysts in biofuel conversion processes, while also emphasizing the need for further catalyst optimization or additional processing stages to achieve complete transformation into fuel-grade hydrocarbons.